Applying the decision aids systems for hydropower expand process - Punys, Petras; Laurinavičius , Eligijus (Lietuvos matematikos rinkinys, 2004)
The ELECTRE method is used for the projects evaluation and outranking. The Nemunas river hydropower station projects are taken into account. The case study of sensitivity analysis on the weighted criteria is presented.
Keywords: multiple criteria; decision making; project ranking